(untitled) (International Journal of Studies in Nursing, 2025)
Background: Empathy in nursing has been shown to positively impact patient outcomes and support nurses’ well-being. However, while this beneficial relationship has been explored in the literature, there remains no established guidelines or optimal instructional methodologies for effectively teaching empathy to nursing students. Objective: This integrative review aims to examine and synthesize innovative instructional methodologies for teaching empathy to undergraduate nursing students. Methods: Guided by the Dhollande et al.’s (2021) framework, a comprehensive Boolean search of CINAHL, PubMed, and PsycINFO was conducted between July 2024 and June 2025. A total of 830 articles were screened, with 33 studies meeting eligibility criteria. Results: Thematic analysis of the included studies yielded four primary domains of instructional methodologies: 1) simulation-based learning, 2) virtual reality experiences, 3) multimodal educational modules, and 4) arts-based interventions. These innovative instructional methodologies positively affected nursing students’ short-term empathy development, clinical readiness, and communication skills. However, findings regarding the long-term efficacy and consistency of empathy fostered across diverse student populations were variable. Conclusions: Empathy education in nursing benefits from multimodal, experiential teaching approaches incorporating emotional reflection and real-world patient perspectives. Sustained empathy development requires reinforcement, structured debriefing, and supportive learning environments. Future research should employ longitudinal designs with validated empathy metrics and examine the translation of empathy gains into clinical behavior.